DESIGN HORIZONTAL AXIS WIND TURBINE WITH THREE BLADES - Winarno, Basuki; basuki, Imam; Safi'i, Ali (Merdeka Malang University, 2018)
The use of energy, especially electrical energy in need once by the public. Lots of alternative energy in Indonesia that can be utilized to generate electrical energy. One of them is wind energy. Wind energy is easy to get especially in coastal areas. Electrical energy is not solely produced by nature. So to take advantage of the wind in need of a tool that can work and produce electricity well. Tools that can be used are windmills. One of them is Horizontal Axis Wind Turbine with Three Blade which will drive the gear box and then rotate the generator. In this wind turbine the material used to make the blade is mindi wood. The wood is quite strong, lightweight and easily obtained by size. The experimental results at a wind speed of 4 - 6 m/s with an angle of 600 at rpm gain on a generator of about 1300 with an output of 15.92VDCDOI :Â https://doi.org/10.26905/jeemecs.v1i1.2076Â